ESPCam Control Using Telegram on ESP32 Microcontroller-Based Security Camera Systems - Aris Sudaryanto; Dimas Sasongko; Agung Kridoyono; Rizqi Putri Nourma Budiarti; Savilla Tifania Mahadewi; Feby Ade Arvianto (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2022)
A security camera must be easy to control, because users need to be able to monitor and control it even when they are in another place. To accommodate this need, security cameras are generally controlled by a computer, then the data is sent to a web server that can be accessed by users. However, the system is quite complicated because it still requires a computer, as well as the additional cost of renting a website server. In this study, computer functions were replaced with the ESP32 microcontroller, and the website server as well as the application interface was replaced with the Telegram BOT. The ESP32 microcontroller was chosen because its function is almost the same as a computer, while the Telegram BOT can be used free of charge. This study focuses on testing the success rate of the system in responding to commands given via the Telegram BOT, with the type of command connecting the Telegram BOT with ESPCam, turning on or off the LED flash, taking pictures, and the combination. Based on the tests that have been carried out for all existing command combinations, with each test being repeated 25 times, it was found that the success rate of the system reached 84.67%.